Analysis of 180 Genetic Variants in a New Interactive FX Variant Database Reveals Novel Insights into FX Deficiency - Harris, Victoria A.; Lin, Weining; Perkins, Stephen J. (TH Open, 2021)
Coagulation factor X (FX), often termed as Stuart–Prower factor, is a plasma glycoprotein composed of the γ-carboxyglutamic acid (GLA) domain, two epidermal growth factor domains (EGF-1 and EGF-2), and the serine protease (SP) domain. FX plays a pivotal role in the coagulation cascade, activating thrombin to promote platelet plug formation and prevent excess blood loss. Genetic variants in FX disrupt coagulation and lead to FX or Stuart–Prower factor deficiency. To better understand the relationship between FX deficiency and disease severity, an interactive FX variant database has been set up at https://www.factorx-db.org, based on earlier web sites for the factor-XI and -IX coagulation proteins. To date (April 2021), we report 427 case reports on FX deficiency corresponding to 180 distinct F10 genetic variants. Of these, 149 are point variants (of which 128 are missense), 22 are deletions, 3 are insertions, and 6 are polymorphisms. FX variants are phenotypically classified as being type I or II. Type-I variants involve the simultaneous reduction of FX coagulant activity (FX:C) and FX antigen levels (FX:Ag), whereas type-II variants involve a reduction in FX:C with normal FX:Ag plasma levels. Both types of variants were distributed throughout the FXa protein structure. Analyses based on residue surface accessibilities showed the most damaging variants to occur at residues with low accessibilities. The interactive FX web database provides a novel easy-to-use resource for clinicians and scientists to improve the understanding of FX deficiency. Guidelines are provided for clinicians who wish to use the database for diagnostic purposes.
Keywords: coagulation factors; hemostasis; protein structure/folding; gene mutations; inherited coagulation disorders